2016
DOI: 10.1097/nmd.0000000000000561
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Social Capital and Depression Among Chinese Older Adults Living in Public Housing

Abstract: Social capital is a critical resource for physical and mental health among older adults, but few studies have investigated this relationship in Chinese populations, and specifically among those with low socioeconomic status. This study examined the association between depression and cognitive social capital (reciprocity and trust) and structural social capital (social participation) in a community sample of older adults living in public housing in Macau (SAR), China (N = 366). Multivariable linear regressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
4
4
0
Order By: Relevance
“…We found that a higher level of social capital was associated with a lower likelihood of experiencing depressive symptoms after adjustment for confounders in the total population, which is consistent with previous studies [6,10,11,27]. Li et al [10] and Han et al [6] showed that a lower level of social capital (concerning trust and reciprocity) was connected associated with suffering from depression among people in their later life.…”
Section: Discussionsupporting
confidence: 91%
“…We found that a higher level of social capital was associated with a lower likelihood of experiencing depressive symptoms after adjustment for confounders in the total population, which is consistent with previous studies [6,10,11,27]. Li et al [10] and Han et al [6] showed that a lower level of social capital (concerning trust and reciprocity) was connected associated with suffering from depression among people in their later life.…”
Section: Discussionsupporting
confidence: 91%
“…We found that a higher level of social capital was associated with a lower likelihood of experiencing depressive disorders after adjustment for confounders in the total population, which is consistent with previous studies [6,10,11,27]. Li et al [10] and Han et al [6] showed that a lower level of social capital (concerning trust and reciprocity) was connected associated with suffering from depression among people in their later life.…”
Section: Discussionsupporting
confidence: 91%
“…Researchers have reported that social capital was related to the improvement of self-rated health [23,24] and the incidence of some diseases like HIV and heart disease [25]. Besides physical health, social capital affects mental health, such as depression [26] and anxiety [27].…”
Section: Introductionmentioning
confidence: 99%